Contradef: A Dynamic Binary Instrumentation Tool for Evasive Malware Analysis - Campelo, Henrique B.; S. Neto, Francisco S.; Feitosa, Eduardo L. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
Contradef is a DBI tool built on Intel Pin. It is designed for analyzing evasive software through tracing techniques. The tool records instruction flows, memory accesses, API calls, and internal states to log files, enabling postexecution analysis. Contradef enables execution, inspection, and even manipulation of software protected by advanced packers like VMProtect, revealing obfuscation and evasion techniques that typically bypass static analysis methods.